Efficacy and safety of Qingre Lishi decoction for type 2 diabetes: a systematic review and meta-analysis - Lin, Zimei; Sun, Yi; Li, Juan; Du, Likun (Frontiers in Endocrinology, 2025)
ObjectiveThis systematic review and meta-analysis aimed to evaluate the efficacy and safety of Qingre Lishi decoction (QRLSD) for type 2 diabetes (T2D), thereby providing new evidence-based insights into the role of traditional Chinese medicine in treating T2D.MethodsWanFang, Embase, Web of Science, PubMed, China National Knowledge Infrastructure, and the Cochrane Library were searched up to January 2025. Studies assessing the efficacy and safety of QRLSD in treating T2D were included. Data were pooled using standardized mean difference (SMD) and risk ratio (RR). Sensitivity and subgroup analyses were performed to assess the stability of the results and investigate potential sources of heterogeneity. Statistical analyses were conducted using RevMan 5.4 and Stata 18.0.ResultsA total of 18 randomized controlled trials (RCTs) were included. Our results showed that QRLSD reduced the levels of fasting blood glucose (SMD: -15.09; 95% CI: [-18.27, -11.90], I² = 99%, P < 0.00001), 2-hour postprandial blood glucose (SMD: -17.71; 95% CI: [-21.70, -13.71], I² = 98%, P < 0.00001), glycated hemoglobin (SMD: -18.93; 95% CI: [-22.77, -15.09], I² = 98%, P < 0.00001), as well as other metabolic parameters, indicators of insulin resistance, and body mass index. No significant difference in the incidence of adverse events between the intervention and control groups was found (RR: 1.8; 95% CI: [0.57, 5.68], I² = 9%, P=0.32).ConclusionFor T2D, QRLSD can significantly improve clinical outcomes and may serve as a more effective therapy than single Western medicine therapy. Moreover, it was not related to significant adverse events. Given the inherent limitations of this study, large-scale, multicenter international RCTs are needed to further validate these findings in the future.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD420251000585.